2020
DOI: 10.1371/journal.pone.0228601
|View full text |Cite
|
Sign up to set email alerts
|

Zimbabwe’s national third-line antiretroviral therapy program: Cohort description and treatment outcomes

Abstract: Background In 2015, Zimbabwe introduced third-line antiretroviral therapy (ART) through four designated treatment centers; three government clinics in Harare and Bulawayo, and Newlands Clinic (NC), operated by a private voluntary organization in Harare. We describe characteristics of patients receiving third line ART and analyzed treatment outcomes in this national programme as of 31 December 2018. Methods We described the population using proportions for categorical variables, and medians and interquartile ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…There was no association between treatment modification and subsequent survival. There is limited literature comparing survival outcomes after secondline treatment failure, however, studies have reported up to 26% mortality among those who have failed but remained on second-line [11] and 5-11% among those who have switched to third-line [3,15,24,25]. Our study observed a mortality rate of 3.9/100PYS for those who did not have a treatment modification, and 3.0/100PYS for those who did without ART interruption.…”
Section: Discussionmentioning
confidence: 50%
“…There was no association between treatment modification and subsequent survival. There is limited literature comparing survival outcomes after secondline treatment failure, however, studies have reported up to 26% mortality among those who have failed but remained on second-line [11] and 5-11% among those who have switched to third-line [3,15,24,25]. Our study observed a mortality rate of 3.9/100PYS for those who did not have a treatment modification, and 3.0/100PYS for those who did without ART interruption.…”
Section: Discussionmentioning
confidence: 50%
“…Out of 102 children and adolescents in Harare with virological failure in 2012, 67.6% had ≥1 clinically significant mutation [ 28 ]. There is increased emphasis on treatment switching in international guidelines [ 29 ], informed by a growing recognition of high resistance rates among ALWH [ 30 ]. In this study the highest prevalence of non‐suppression, by far, was in District 1, a border town with high HIV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Lessons drawn from this study, therefore, can be applied to the rest of centres that provide TB services. The urban polyclinics had limited capacity in diagnosing, yet the volume of patients on treatment was similar to hospitals [ 10 ].…”
Section: Discussionmentioning
confidence: 99%